Improving Students' Reading Skills through the Use of the WFR Activities - Tatiana Mikhailova (Asociación Colombiana de Profesores de Ingles, 2008)
This Article entitled Improving Students' Reading Skills through the Use of the WFR Activities is just a very short description of an action research carried out in a public school in Bucaramanga. It is related to the specific pre-reading materials and activities that can be used in an EFL classroom in order to increase and improve learners' pre-reading and reading skills. This article intends to contribute the general observations and results of the research so every EFL teacher can get familiar with some new ideas and, possibly, conceptions about the creative use of the pre-reading materials and activities in EFL classrooms.